If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9p + 11 = 5p + -5 Reorder the terms: 11 + 9p = 5p + -5 Reorder the terms: 11 + 9p = -5 + 5p Solving 11 + 9p = -5 + 5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. 11 + 9p + -5p = -5 + 5p + -5p Combine like terms: 9p + -5p = 4p 11 + 4p = -5 + 5p + -5p Combine like terms: 5p + -5p = 0 11 + 4p = -5 + 0 11 + 4p = -5 Add '-11' to each side of the equation. 11 + -11 + 4p = -5 + -11 Combine like terms: 11 + -11 = 0 0 + 4p = -5 + -11 4p = -5 + -11 Combine like terms: -5 + -11 = -16 4p = -16 Divide each side by '4'. p = -4 Simplifying p = -4
| 7f-6(f-3)=17 | | 1xy=-12 | | 7(k+4)-6k=28 | | 14=22-0.66x | | 4.4k=29.48 | | (-8y+1)-(-7y-6)=4 | | 7d*3e= | | -20x+20y=100 | | 8e-13=13 | | 8e-13=2 | | 5/x-1+4x/x+1=4 | | 12(3x+3)-5(2x-5)=6x-59 | | 7/5-9/2b= | | log(8)(7)+log(8)(11)=log(8) | | 5a-2(2+a)+3a= | | log(8)(7)+log(8)(11)= | | 2+b(4b)=22 | | -4(2n-7)= | | x^5+x^3+55=0 | | (x+5)(x+5)=-64 | | 2(y-6)+12=24 | | 10-4x+3=6x+5-7x | | -6k-k=45 | | X^2+xy^2+y^2=1 | | 6x^2-6x+10=2x^2+2x+25 | | h^2-8h+1=0 | | 7w+11=3w+4(w+2) | | 9x-14=3x+9 | | -3x=7+6y | | x^4+0x^3-9x^2+0x+8=0 | | 2/3(6-3/2) | | 2x+7y=42 |